Cytotoxicity and genotoxicity of light emitted by incandescent, halogen, and LED bulbs on ARPE-19 and BEAS-2B cell lines. Issue 19 (2nd October 2018) - Gea, Marta; Schilirò, Tiziana; Iacomussi, Paola; Degan, Raffaella; Bonetta, Sara; Gilli, Giorgio
ABSTRACT: LED technology has the extraordinary ability to reduce energy consumption, constituting an economic and ecological advantage, so it is planned to replace incandescent, halogen and other inefficient bulbs for public and domestic lighting with LEDs. LEDs present specific spectral and energetic characteristics compared with those of other domestic light sources, so the potential risks for human health of these bulbs need to be explored. The aim of this study was to assess cytotoxicity and genotoxicity of light emitted by different commercial light bulbs: incandescent, halogen, and two LED bulbs with different correlated color temperatures. The evaluation was done on ARPE-19 as a specific cell model for eye toxicity and on BEAS-2B as a good cell model for toxicology tests. Light induced mainly cytotoxic effects on ARPE-19 and DNA damage on BEAS-2B, so different cell lines showed different biological responses. Moreover, our findings indicate that among the four bulbs, cold LED caused the highest cytotoxic effect on ARPE-19 and the highest genotoxic and oxidative effect on BEAS-2B. Cold LED is probably able to cause more cellular damage because it contains more high-energy radiations (blue). These results suggest that LED technology could be a safe alternative to older technologies, but the use of warm LED should be preferred to cold LED, which can potentially cause adverse effects on retinal cells.